IN SILICO STUDY OF PRIMER AND PROBE DESIGN FOR PORCINE DNA DETECTION IN PHARMACEUTICAL PRODUCTS USING QUANTITATIVE PCR - Berliana Nur Rifa, Shallya
Due to absolute halal law, the parameters of sensitivity and specificity become essential when it comes to porcine detection in pharmaceutical products. As a part of the requirements of halal products, the existence of porcine is strictly prohibited even in minute quantities, either as a whole part or its derivative compounds. Therefore, a sensitive and specific method is indispensable to detect the porcine content from any boar species even in the slightest quantities. As an option, quantitative PCR (qPCR) is one of the methods that is commonly used to detect porcine DNA in pharmaceutical products due to the reliable sensitivity and specificity that is offered. However, the specificity of qPCR can be improved by using compatible primer and probe designs. Therefore, this in silico study aimed to produce primers and probe designs with acceptable specificity and sensitivity to detect porcine DNA in pharmaceutical products through evaluation of its characteristics, attachment ability, cross homology, and specificity. Three candidate primers and probes were designed by targeting the cytochrome B (CYTB) gene from Sus scrofa mitochondrial DNA. All of 3 candidates were evaluated based on its characteristics, attachment ability, cross homology, and specificity. This evaluation was also performed on ISO/TS 20224-3 (ISO) and the EasyFast™ #EFPig100 kit (kit) primers and probes as the comparison subject. As the result of the evaluation series, the best primer and probe designs were forward primer 2 (5’ AGGAGACCCAGACAACTACA 3’), reverse primer 2 (5’ CGTAGAATAGCGTAGGCGAATAA 3’), and probe 2 (5’ CCCAGCAAACCCACTAAACACCC 3’). Furthermore, designed primer and probe should be further validated by optimizing qPCR conditions such as annealing temperature and the concentration that needed to be use for detecting porcine with qPCR. Through the lab experiment, it is also necessary to evaluate the specificity of the attachment to prove that the primers and probes produce the right amplicons, for instance with the melting curve method, gel electrophoresis, and sequencing. In addition, the designed primers and probes should be tested on subjects other than S. scrofa, S. celebensis, B. taurus, O. aries, and C. lupus to improve the knowing of its specificity.